2013
DOI: 10.4028/www.scientific.net/amr.631-632.172
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Transfer Film and Tribological Properties of Oxide/PTFE Composites

Abstract: The formed transfer film on the counterpart surface and tribological properties of PTFE composites filled with Al2O3 or SiO2 were investigated in this paper. The results indicated that under the same friction conditions, the friction coefficients of SiO2/PTFE and Al2O3/PTFE are very close to each other, but the wear resistance of SiO2/PTFE is superior to that of Al2O3/PTFE. According to the measured data, the micro-hardness and elastic modulus of the transfer film for SiO2/PTFE are much better than those of Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Therefore, we use a bonding force to express the combined effect of various factors (including tribophysical, tribochemical and tribomechanical effects) on the transfer film (i.e. the bonding strength between the transfer film and the matrix), and the determination of this parameter is based on the related experimental results (Bahadur and Sunkara, 2005; Xie et al , 2013). Bahadur and Sunkara (2005) noted that there is a range of the strength of the bond between the transfer film and the counterface, according to the different kinds of the materials.…”
Section: Numerical Simulation Of the Friction Transfer And Wearmentioning
confidence: 99%
“…Therefore, we use a bonding force to express the combined effect of various factors (including tribophysical, tribochemical and tribomechanical effects) on the transfer film (i.e. the bonding strength between the transfer film and the matrix), and the determination of this parameter is based on the related experimental results (Bahadur and Sunkara, 2005; Xie et al , 2013). Bahadur and Sunkara (2005) noted that there is a range of the strength of the bond between the transfer film and the counterface, according to the different kinds of the materials.…”
Section: Numerical Simulation Of the Friction Transfer And Wearmentioning
confidence: 99%
“…Whereas the composite contained clear regions of high and low hardness from the epoxy and PTFE, respectively, the wear surface exhibited uniformly low hardness, suggesting that a running film of PTFE was preferentially drawn over the entire surface; these PTFE running films were thought to substantially decrease friction and wear by preventing adhesion between the epoxy phase and the counterbody. Xie et al [57,58] measured two particle-filled PTFE microcomposite transfer films using nanoindentation and found the lower wear system has a slightly softer and more adhesive transfer film. The fact that transfer films can become harder or softer than either constituent reflects the complicated and yet uncertain role of transfer films in friction and wear control.…”
Section: Mechanical Properties Of the Transfer Filmmentioning
confidence: 99%
“…The adhesion strength between transfer films and counterfaces is among the most frequently discussed mechanisms of wear reduction for polymeric solid lubricants [3,[8][9][10][58][59][60][61][62]. Adhesion is often thought of in terms of bonding and may have physical or chemical origins [44,[63][64][65][66][67].…”
Section: Adhesion Of the Transfer Filmmentioning
confidence: 99%
“…The literature indicated that when the temperature is higher than the melting point of the binder, the fluorinated polymer coating would be stratified, that is, the polyacrylate is near the substrate, while the PTFE is distributed in the upper layer. This stratified structure would be beneficial to the improvement of adhesion strength, and the transfer film with better adhesion strength as well as mechanical property is reported to be useful to enhance the tribological properties of the composite . (2) The mechanism of hard fillers to improve the wear resistance of PTFE is mainly attributed to the preferential load supporting capacity .…”
Section: Resultsmentioning
confidence: 99%